2002
DOI: 10.1023/a:1016293904149
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Experiments on two mouse strains with opposite reactions to emotional stress showed selectivity of the anxiolytic effect of endogenous dipeptide cycloprolylglycine. In the open field test cycloprolylglycine (0.01-0.10 mg/kg intraperitoneally) dose-dependently (1.8-2.1-fold) increased motor activity of BALB/c mice with manifest fear reaction and had no effect on C57Bl/6 mice with active behavior. The content of endogenous cycloprolylglycine in mouse brain correlated with the type of emotional stress reaction: i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In vitro studies showed that dipeptides thymogen, Vilon, and Bestim in low concentrations exhibit immunomodulatory activity [1,6,7,12]. Short peptides are considered as possible universal regulators of vital functions in the organism [1,9,12].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies showed that dipeptides thymogen, Vilon, and Bestim in low concentrations exhibit immunomodulatory activity [1,6,7,12]. Short peptides are considered as possible universal regulators of vital functions in the organism [1,9,12].…”
Section: Resultsmentioning
confidence: 99%
“…CPG content was found to depend on the type of emotional stress reaction of the animals. CPG content in the whole brain of stress-resistant С57Bl/6 mice was 1.5 times higher than in non-stress-resistant Вalb/c mice [8]. This suggests that CPG plays a role of endogenous anxiolytic agent.…”
mentioning
confidence: 86%
“…In addition, CPG possessed in vitro anticoagulant and fi brinolytic properties in concentrations of 10 -5 -10 -10 М and modulates membrane potential in synaptoneurosomes in concentration 10 -6 М [5,7]. In experiments on rats, CPG exhibits anxiolytic activity in elevated plus maze test in doses of 0.05-0.10 mg/kg intraperitoneally [3] and in open fi eld test in doses of 0.01-0.10 mg/kg [8]. Anxiolytic effect of CPG is selective.…”
mentioning
confidence: 99%
“…The in vivo investigations of cyclo (Pro—Gly) showed that this dipeptide has pharmacological profile resemble that of Piracetam. Like Piracetam, cyclo (Pro—Gly) possess nootropic [22], neuroprotective, antihypoxic [23] and anxiolytic [24] activities. Evaluation of the effect on memory phases in passive avoidance test in rats demonstrated that cyclo (Pro—Gly) similar to Piracetam is active only when administered before learning.…”
Section: Noopept a Dipeptide Nootropic Drugmentioning
confidence: 99%